Птицы - Бабенко Владимир Григорьевич (Детская энциклопедия РОСМЭН, 2014)
Экземпляры: ф.4 (20171117) / Инвентарный номер: 2788 / Цена: / Сис.шифр: 28.6я2 / Авт.знак: Б 12 / ГРНТИ: 34.33 / ББК: 28.693.35я2